2012
DOI: 10.1111/j.1469-7580.2012.01513.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the potential value of individual parameters of histological grading systems in a sheep model of cartilage damage: the Modified Mankin method

Abstract: A total histological grade does not necessarily distinguish between different manifestations of cartilage damage or degeneration. An accurate and reliable histological assessment method is required to separate normal and pathological tissue within a joint during treatment of degenerative joint conditions and to sub-classify the latter in meaningful ways. The Modified Mankin method may be adaptable for this purpose. We investigated how much detail may be lost by assigning one composite score ⁄ grade to represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 20 publications
(15 reference statements)
0
23
0
Order By: Relevance
“…Highlighting these potential differences, a 2012 study by Moody et al found significant variability in the morphology of OA progression between ovine ACLT/medial collateral ligament transection, meniscectomy, and ACL core models, as measured by differences in the parametric scores assigned during modified Mankin grading (19). The variability in these results embodies the challenge in selecting any one animal surgical OA model as the one most representative of OA.…”
Section: Aclt Acl Reconstructionmentioning
confidence: 99%
“…Highlighting these potential differences, a 2012 study by Moody et al found significant variability in the morphology of OA progression between ovine ACLT/medial collateral ligament transection, meniscectomy, and ACL core models, as measured by differences in the parametric scores assigned during modified Mankin grading (19). The variability in these results embodies the challenge in selecting any one animal surgical OA model as the one most representative of OA.…”
Section: Aclt Acl Reconstructionmentioning
confidence: 99%
“…; Moody et al. ) is, arguably, the most widely used method to assess the severity of OA in human tissue biopsies, in tissue removed during joint replacement, and in animal models to allow for comparison across species. The Osteoarthritis Research Society International's Cartilage Histopathology Assessment System (OOCHAS) (Pritzker et al.…”
Section: Introductionmentioning
confidence: 99%
“…The most frequently used surgical models in both species involve destabilization or removal of a meniscus; forced exercise after surgical intervention has been demonstrated to worsen OA lesions when compared to surgery alone. 7,8,22 In contrast to that of other species, transection of the ACL alone results in only mild cartilage pathology, 80,87,102 and an attempt to mimic posterolateral instability via transection of the popliteus tendon, lateral collateral ligament, and lateral joint capsule transection in goats resulted in no macroscopic and minimal histologic lesions. 107 These findings emphasize that biomechanical and anatomic differences do exist between sheep/goats and humans that may limit translation of some experimental results.…”
mentioning
confidence: 99%
“…80 A recent study raised concerns about the current use of this system when comparing different OA models by demonstrating, for example, that the same global score can be achieved with focal deep cartilage damage and minor matrix degeneration, or by more modest structural damage but extensive cellular changes and proteoglycan loss. 102 As a result, the authors suggested that evaluation of the individual parameters of the modified Mankin system may yield more useful information about pathophysiology of disease than the global score alone. 102 It should be noted that macroscopic scoring systems exist specifically for evaluating cartilage repair in sheep and goats.…”
mentioning
confidence: 99%
See 1 more Smart Citation